(untitled) (المجلة الدولية للبحوث العلمية, 2023)
Biomedical optics has emerged as a dynamic field encompassing a range of optical devices and technologies, including light sources, lasers, sensors, optical fibers, and optical processing principles. Its impact on medical engineering and clinical applications has been profound, leading to advancements in laboratory practices, optical fibers, biosensing, imaging, radiation grading, absorption spectroscopy, and polarization sensing. This article examines the historical progression of biomedical optics, highlighting its contributions to medical imaging and diagnosis. It focuses particularly on computed tomography, fluorescence imaging, optical molecular imaging, spectroscopy, near-infrared tomography, and optical coherence techniques. Biomedical optics’ development has transformed medical science by enabling non-invasive diagnosis, improving treatment planning, and enabling specific therapy. The positive outcomes of these advancements underscore the significance of biomedical optics in promoting progress in the field of medicine. The paper discusses optical technologies and their clinical implications, including spectroscopy, near-infrared tomography, optical coherence tomography, computed tomography, fluorescence imaging, and molecular imaging.